Student Careers: What Factors Influence Career Choice? - Hadiyati, Muftiah Azizi; Astuti, Budi (Journal of Education Reseach and Evaluation, 2023)
High school age or adolescence is in the exploration stage where at this stage students should already focus on determining careers in a more specific range, but not a final choice. The success of education obtained by individuals is one of the keys to the success of the state. In education, various things are taught to become the provision of individuals in the future. This research is motivated by the low career choices of students while determining a career is very important for their future. The purpose of this research is to analyze the factors that influence students' career choices. This type of research is qualitative. The data in this study were obtained through interviews, observations, and documentation. The type of data analysis used is descriptive and qualitative analysis. Based on the data obtained from the research subjects, it shows that there are four factors that influence students' career choices, namely, intelligence and special talents (all three students are influenced), interest in careers (all three students are influenced), personality (both students are influenced), and family background and socioeconomic status (all three students are influenced). So the conclusion is that the factors that influence students' career choices are from themselves and their families.